Alterations of detraining of handball players aged 17-18 years during five and ten weeks of transition period - Skarbalius, A.; Astrauskas, M. (Education. Physical training. Sport, 2000)
The aim of the paper was to establish the influence of five and ten weeks long passive rest and low level of physical activity undertaken for five weeks during the transition period on sports fitness of handball players aged 17-18 years. Two experimental groups and one control group of handball players 17-18 years old, each group comprising 7 subjects, were studied. The duration of the transition period in the case of both experimental groups was five weeks. The physical activities of the first experimental group (E-1) were two trainings per week (during five weeks). The second experimental group (E-2) took a passive rest for five weeks. During the transition period the control group had a passive rest for ten weeks (the time corresponding to the duration of school leave). The groups were studied at the beginning of the transition period (in the month of June) and at the end of the transition period (in the months of August and September). Sports fitness of handball players was evaluated on the basis of indices of physical development as well as those of physical and technical fitness. According to the results of our study there were but slight changes (p>0.05) in the indices of speed and power (the high jump). Physical activities (two times per week) undertaken by handball players of the E-1 group allowed them to improve the indices of strength endurance by as many as 6.2 per cent (p>0.05). Physical activities of moderate intensity undertaken for five weeks had a positive influence on maintaining the level of endurance of the physical quality achieved as well as created preconditions for handball players of the E-1 group to retain the physical properties of speed, force of speed and force rate. The indices of technical fitness of the control group grew worse by 7.25% on average, those of the E-2 group - by 5.5%, whereas the indices of the E-1 group even improved (in particular the indices of catching and passing that improved by 3.2% and those of accuracy - even by 20.6% on average). The results of our study allow us to assert that a passive rest of five weeks had the greatest influence on the detraining of indices of technical fitness and functional capacity. Physical activity (two times per week during five weeks) decreased the process of deadaptation and created favourable prerequisites for retaining the level of sports fitness possessed. Such alterations in the indices of technical fitness are indicative of the fact that physical activities of moderate intensity undertaken for five weeks allowed to improve accuracy, i.e. the actions requiring motoric abilities. Conversely, the efficiency of handball actions the performance of which is determined by physical properties decreased. The research carried out has posed the question - what should the duration and content of the transition period for handball players be depending on the level of training possessed? Further research will be aimed at establishing the optimal parametres of the duration and content of the transition period for handball players.